The Effect of Buddhist Character Education and Self-Confidence on Student Learning Motivation at Maitreyawira Students, Pekanbaru - Bie Na; Budi Utomo; Kabri Kabri (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Learning motivation is very important for university students because it can enhance enthusiasm, learning outcomes, and the achievement of academic goals. High motivation encourages students to study harder, overcome challenges, and achieve success in education. The purpose of this research is to determine the effect of both Buddhist character education and self-confidence on the learning motivation of STAB Maitreyawira Pekanbaru students. This research uses a quantitative method with a correlational research design. The sample was determined using a simple random sampling technique, with a total of 110 students. Data collection instruments were in the form of closed questionnaires distributed via Google Forms. The results of the questionnaires were tested through instrument testing, classical assumption testing, and simple and multiple regression correlation analysis. The results of the study show that: (1) Buddhist character education has a positive effect on learning motivation. (2) Self-confidence has a positive effect on learning motivation. (3) Buddhist character education and self-confidence both have a positive effect on learning motivation.In conclusion, based on the research findingsthat students' learning motivation can be improved through Buddhist character education and self-confidence.